(untitled) (International Journal of Chemical and Process Engineering Research, 2014)
Equilibrium, kinetics and thermodynamic studies on the removal of Acid Red (AR88) using Ulva reticulata have been investigated. In batch experiments, the parameters studied included the effect of the dye concentration, temperature, contact time, adsorbent dosage, pH. The pseudo-first-order and pseudo-second-order kinetic data were tested with experimental data. The optimum conditions were: pH 5, temperature 30ºC, biomass size 0.5 mm and maximum metal uptake was 75.4 mg/g .Various thermodynamic parameters such as ∆Hº, ∆Gº and ∆Sº were calculated indicating that the present system was spontaneous and endothermic process. The pseudo first and second order kinetic models were also applied to the experimental kinetic data obtained during Biosorption of AR88 and High correlation coefficients with low standard deviations favor the pseudo-second-order model for the present systems. The ability of Ulva reticulata to Biosorption AR88 in a packed column was investigated, as well. A glass column was used to conduct the experiments. At 20 cm (bed height), 5 ml/min (flow rate) and 100 mg/L (initial concentrations), ulva reticulata exhibited AR88 uptake of 88.65 mg/g. The Thomas model was used to predict the breakthrough curves.